Dual-band mixed-mode bandpass filter based on dual-layer substrate integrated waveguide resonator loaded with A capacitive patch - Rihui Zeng; Jianpei Chen; Xia Luo; Dongya Shen; Chuanxi Xing (PLoS ONE, 2025)
To address the growing demand for compact and high-performance microwave filters in modern communication systems, a mixed-mode bandpass filter is proposed in the article. A dual-layer substrate integrated waveguide resonator loaded with a capacitive patch (CP-DSIWR) is proposed and theoretically analyzed, with both patch modes and cavity modes existing. To construct the bandpass filter, two rows of metallic vias are designed in the CP-SIWR to enable coupling between the two types of the modes, with the structure being fed by microstrip line. A slot is embedded in the center of the capacitive patch to tune the resonant frequencies. The simulated results of the filter show that TM01, TM10 and TE101 modes are excited, achieving a dual-band filtering response with tunable frequency characteristics. The filter is centered at 6.2 GHz and 12.9 GHz with a compact size of 0.57λg×0.57λg. A prototype is fabricated and measured for validation, showing good agreement between the simulation and measured results.